The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1037/int0000166
|View full text |Cite
|
Sign up to set email alerts
|

Responding to inappropriate client sexual behaviors: Perspectives on effective supervision.

Abstract: Inappropriate client sexual behaviors, including verbal remarks and inappropriate physical contact, are a common but challenging aspect of clinical practice. Trainees may not know how to address client sexual behaviors effectively, and supervisees often limit or avoid disclosing inappropriate client behaviors in supervision, reducing the likelihood of obtaining helpful guidance. The present article details supervisor practices that can facilitate trainee disclosure of inappropriate client sexual behaviors, ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Deciding how to respond to sexual harassment can be difficult for trainees. Female trainees experiencing sexual harassment not only have to respond at the moment to these behaviors with limited training but also negotiate other hard decisions afterward, such as whether to report these incidents to their supervisors or others in their institution (Thompson, 2020). Other decisions that need to be made include seeking support and/or navigating organizational policies.…”
Section: Abstract: Gender Training Supervision Sexual Harassment Disc...mentioning
confidence: 99%
“…Deciding how to respond to sexual harassment can be difficult for trainees. Female trainees experiencing sexual harassment not only have to respond at the moment to these behaviors with limited training but also negotiate other hard decisions afterward, such as whether to report these incidents to their supervisors or others in their institution (Thompson, 2020). Other decisions that need to be made include seeking support and/or navigating organizational policies.…”
Section: Abstract: Gender Training Supervision Sexual Harassment Disc...mentioning
confidence: 99%
“…Faculty can encourage students’ sex-positive research interests and mentor them in best practices. Clinical supervisors can move beyond covering sexuality only as it pertains to navigating sexual attraction or sexually harassing behavior in the supervisory relationship or with clients (Ladany et al, 2005; Thompson, 2020) and model inviting and attending to sex and sexuality as it relates to clients’ well-being. Finally, given that educators in health service psychology often report little sexuality education in their own training (Mollen, Burnes, et al, 2018), which may inhibit their ability to facilitate trainees’ education, faculty and trainers can pursue continuing education via professional organizations including American Association for Sexuality Educators, Clinicians, and Trainers (AASECT) or the World Association for Sexual Health (WAS).…”
Section: Sex Education In the United Statesmentioning
confidence: 99%
“…Across the articles in this special issue, there are some commonalities that suggest areas for growth. For example, despite the increasing emphasis on multicultural considerations in psychotherapy (Gatmon et al, 2001; Phillips, Parent, Dozier, & Jackson, 2017; Soheilian, Inman, Klinger, Isenberg, & Kulp, 2014), many of the personal narratives in this special issue reflect upon microaggressions, discrimination, and otherwise marginalizing comments during supervision that negatively impacted supervisees (Hagler, 2020; Thompson, 2020; Valmas, Himrich, & Finn, 2020; Williams & Raney, 2020) and their work with clients (Williams Kapten, 2020). Consistent with those narratives, recent research has found that supervisees from underrepresented groups are much more likely to experience their supervisor as insufficiently valuing diversity and in need of improvement in multicultural competencies (Gregus, Stevens, Seivert, Tucker, & Callahan, 2019).…”
Section: Fit Of Special Issue Articles With the Extant Empirical Lite...mentioning
confidence: 99%
“…In this issue, Constrastano (2020) captures the complexity and confusing nuances associated with professional boundary crossing by a supervisor and highlights the consequent impact on the supervisory alliance. Further, across the personal narratives in this special issue, multiple supervisors are recalled as having a negative impact on female supervisees’ professional development, and their ability to respond to inappropriate client sexual behaviors (Thompson, 2020) or other boundary violations in psychotherapy (Valmas et al, 2020).…”
Section: Fit Of Special Issue Articles With the Extant Empirical Lite...mentioning
confidence: 99%